2017
DOI: 10.1002/lrh2.10047
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perspectives regarding alternate approaches to informed consent for comparative effectiveness research

Abstract: Introduction Traditional informed consent approaches, involving separate discussions and lengthy consent forms, may be an imperfect fit for comparative effectiveness research (CER) that is integrated into usual care and compares non‐investigational treatments. However, systematic efforts to collect broad stakeholder perspectives about alternative streamlined approaches to disclosure and consent in this context have been limited. Methods We used a deliberative engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The ethics of alteration or waiver of consent for pragmatic trials have received considerable attention. 26 , 62 , 63 , 64 , 65 Much of the debate focuses on how the risk of research is assessed in clinical trials. When trials evaluate novel therapies (eg, a new surgical technique) or therapies with substantial prior evidence of superiority, trial participation includes clear potential risks and benefits.…”
Section: Pragmatic Trialsmentioning
confidence: 99%
“…The ethics of alteration or waiver of consent for pragmatic trials have received considerable attention. 26 , 62 , 63 , 64 , 65 Much of the debate focuses on how the risk of research is assessed in clinical trials. When trials evaluate novel therapies (eg, a new surgical technique) or therapies with substantial prior evidence of superiority, trial participation includes clear potential risks and benefits.…”
Section: Pragmatic Trialsmentioning
confidence: 99%
“…Similarly, in a companion study to the Kass et al deliberative engagement study with patients, one of us (Stephanie Morain) reported, with colleagues, that a multistakeholder group—including clinicians, those responsible for ethical and regulatory research oversight, CER researchers, health system administrators, payers, and research funders—voiced strong support (80 percent) for a general notification approach to an observational study of antihypertensives. Support for general notification did not, however, persist among these same stakeholders in the context of a randomized interventional study 38 . Collectively, the findings of Kraft et al and Morain et al suggest that the views of the public may not accord with those of other stakeholders.…”
Section: Empirical Data On Approaches To Consent For Pragmatic Researchmentioning
confidence: 88%
“…Faden and colleagues highlight the strong ethical arguments in favour of streamlining consent procedures in this area and the acceptability to stakeholders of the same. [24][25][26] In this study, we will investigate moving the point at which consent is obtained proximally, away from the final application of eligibility criteria and randomisation. A future model might see patients routinely consented for a range of potential trials (under a specific operational framework such as that suggested by Fiore and Lavori 14 ) on admission to hospital, before it is known whether or not they will be eligible.…”
Section: Pre-emptive and Opt-out Consentmentioning
confidence: 99%
“…There is ongoing debate as to the most appropriate consent mechanisms for facilitating comparative effectiveness research, specifically, for treatments with demonstrable variation already present in their routine use. Faden and colleagues highlight the strong ethical arguments in favour of streamlining consent procedures in this area and the acceptability to stakeholders of the same 24–26…”
Section: Introductionmentioning
confidence: 99%